The Effect of Compensation Disclosure on Compensation Benchmarking: Evidence From China. (April 2018) - Jiang, Wei; Liao, Xinxin; Lin, Bingxuan; Liu, Yunguo
Improved compensation disclosure should increase the efficiency of executive compensation contracts through better benchmarking with peer groups even though managers might try to influence this process through a selective choice of peers. Using a sample of Chinese companies, we find that industry benchmarking is prevalent in China. Moreover, as the regulation for executive compensation disclosure was amended in 2005, executives whose compensation is above the industry average have experienced much smaller pay rises, and executives whose compensation is below the industry average have had much higher pay raises. The results of our study are robust after controlling for various firm and industry characteristics. The results also show that companies controlled by different entities (i.e., central government, local government, or nongovernment) behave very differently in response to enhanced compensation disclosure. These findings highlight the importance of policymakers understanding how different firms react to improved disclosure.